VARIASI POLA SIDIK JARI PETANI DI KAWASAN BEDUGUL, DAN NELAYAN DI KAWASAN PERANCAK PROVINSI BALI: VARIATIONS IN FINGERPRINT PATTERNS OF FARMERS IN THE BEDUGUL AREA, AND FISHERMEN IN THE PERANCAK AREA, BALI PROVINCE - Vandi Dama Setiawan; Made Pharmawati; Ida Bagus Made Suaskara (SIMBIOSIS, 2025)
ABSTRACT Fingerprints are one of the biometric systems currently available besides retina, eye, face and other biometric systems. Fingerprints can be divided into several patterns, namely loop, whorl and arch patterns. The aim of this research is to determine variations in fingerprint patterns in the Bedugul area and fishermen in the Perancak area, Bali Province. The sampling method used was the Purposive Sampling method by taking fingerprint samples from farmers in the Bedugul area and fishermen in the Perancak area. The variables observed were the fingerprint pattern and the number of finger tendrils on the proband's hand. The data obtained will be analyzed by calculating the Furuhata Index, Dankmeijer Index and Total Ridge Count. The results showed that fingerprint patterns, the Furuhata Index and the Dankmeijer Index were not different between male fishermen and female fishermen in Jembrana. Likewise, women farmers in Bedugul have fingerprint types that are no different from men. There are differences in the fingerprint patterns of the fishermen population in Jembrana and farmer in Bedugul. There is no difference in total ridge between fishermen in Jembrana and farmers in Bedugul.